FINANCING IN THE TRAINING OF HEALTH PROFESSIONALS FROM THE PERSPECTIVE OF THE PUBLIC SECTOR, 2016-2018: FINANCIAMIENTO EN LA CAPACITACIÓN DE LOS PROFESIONALES EN SALUD BAJO LA PERSPECTIVA DEL SECTOR PÚBLICO, 2016-2018 - Escobedo Palza, Seimer (2019)
Objective: To estimate the funding and unit cost in the long-term training of health professionals in Peru. Methods: A partial economic evaluation (cost analysis) was carried out from the perspective of the public financier. For financing, reports are shown by budget categories and budget programs of the health sector. Data was obtained through the Integrated System of Financial Administration of the Ministry of Economy and Finance (SIAF-MEF) between the years 2016 - 2018. In relation to the analysis The cost was estimated using the absorption costing methodology. The data was obtained from the Integrated System of Administrative Management (SIGA) - logistic module to obtain the prices of the inputs, the Computer Application of Human Resources of Public Servants (AIRHSP) for salaries of human resources. Results: Financing made by the country in relation to training is estimated at 27 million soles for 2016, and it is reduced to 20 million soles by 2018. The per capita cost for graduates was S /. 12 661 (USD 3 836) and for the specialization it was S /. 23 356 (USD 7 077). Conclusion: Financing in the formation of human resources in health is vital for the achievement of health objectives in Peru. However, there is a decrease in the budget allocated to training activities in the last 3 years.